ChemInform Abstract: Catalyst‐Controlled Regio‐ and Stereoselective Synthesis of Diverse 12H‐6, 12‐Methanodibenzo[d, g][1, 3]dioxocines. Issue 48 (2nd December 2014) - Xia, Likai; Cai, Hongyun; Lee, Yong Rok
Abstract Title compounds (III), (VI), and (VII) are prepared via ethylenediammonium diacetate or TosOH‐catalyzed cascade reactions between resorcinols (I) and (IV) and 2‐hydroxychalcones (II) and (V), respectively.